The Influence of Profitability Leverage and Company Size on Stock Prices in Energy Companies on IDX - Indradewa, Rhian; Sri Damayanti, Alia (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
In a company, three main performance aspects are analyzed: market performance, financial performance, and shareholder value performance. Maximizing company value can enhance shareholder wealth. This study aims to analyze the effect of profitability, leverage, and company size on stock prices in coal sub-sector mining companies. The independent variables in this study are NPM, ROA, ROE, DER, and company size. A quantitative research method is employed, with stock prices as the dependent variable. The sample consists of 24 mining companies listed on the IDX during the 2022–2024 period. The data analysis method used is multiple linear regression analysis. The results of the multiple linear regression analysis indicate that NPM and DER have a negative effect on stock prices, while ROA, ROE, and company size have a positive effect. The R-square value in this study is 0.2782, meaning that the independent variables explain 27.82% of the variation in stock prices, while the remaining 72.18% is influenced by other variables not examined in this study. Based on these findings, it is recommended that management maintain the company’s economic stability to prevent stock price declines.